A Systematic Quality Review of Technology-Aided Reading Interventions for Students With Autism Spectrum Disorder. (December 2022) - Kim, So Yeon; Rispoli, Mandy; Mason, Rose A.; Lory, Catharine; Gregori, Emily; Roberts, Carly A.; Whitford, Denise; David, Marie
Technology has been widely used to teach reading skills to students with autism spectrum disorder (ASD), but the quality of research backing up this practice has not yet been fully investigated. The purpose of this review was to examine the quality of research on technology-aided reading interventions for students with ASD and summarize study characteristics of research studies with meeting the What Works Clearinghouse (WWC) design standards. A total of 31 studies using group design ( n = 4) or single-case design ( n = 27) were systematically aggregated, and 16 studies (52%) met the WWC design standards. Study features related to participants, intervention, technology usage, and outcome variables were synthesized for these 16 studies. Results indicated that two types of technology (i.e., computer, iPad) were used to deliver reading instruction through software programs or support interventionist-directed reading instruction. Finally, implications for research and practice are discussed.